2020
DOI: 10.1021/jacs.0c05219
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of a Heroin Vaccine through Hapten Deuteration

Abstract: The United States is in the midst of an unprecedented epidemic of opioid substance use disorder, and while pharmacotherapies including opioid agonists and antagonists have shown success, they can be inadequate and frequently result in high recidivism. With these challenges facing opioid use disorder treatments immunopharmacotherapy is being explored as an alternative therapy option and is based upon antibody−opioid sequestering to block brain entry. Development of a heroin vaccine has become a major research f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Similarly, the binding of nicotine to a nicotine-specific Fab was largely driven by hydrophobic contact with the nicotine rings including the charged pyrrolidine nitrogen . In support of this hypothesis, minimal modifications of hapten structures such as fluorination or deuteration , seem to impact vaccine efficacy against their respective drug targets. It has been consistently shown that oxycodone is a more immunogenic hapten core than hydrocodone, despite a minor structural difference consisting of a -OH vs -H at the C14 position on the morphinan structure. , Differences between the original pharmacophore and the cognate hapten structure may alter their ability to engage the BCR of hapten-specific B cells, as supported by evidence that a higher frequency of B cells specific for oxycodone-based haptens is found in the murine preimmunization repertoire compared to hydrocodone-based haptens .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Similarly, the binding of nicotine to a nicotine-specific Fab was largely driven by hydrophobic contact with the nicotine rings including the charged pyrrolidine nitrogen . In support of this hypothesis, minimal modifications of hapten structures such as fluorination or deuteration , seem to impact vaccine efficacy against their respective drug targets. It has been consistently shown that oxycodone is a more immunogenic hapten core than hydrocodone, despite a minor structural difference consisting of a -OH vs -H at the C14 position on the morphinan structure. , Differences between the original pharmacophore and the cognate hapten structure may alter their ability to engage the BCR of hapten-specific B cells, as supported by evidence that a higher frequency of B cells specific for oxycodone-based haptens is found in the murine preimmunization repertoire compared to hydrocodone-based haptens .…”
Section: Discussionmentioning
confidence: 86%
“…64 Similarly, the binding of nicotine to a nicotine-specific Fab was largely driven by hydrophobic contact with the nicotine rings including the charged pyrrolidine nitrogen. 65 In support of this hypothesis, minimal modifications of hapten structures such as fluorination or deuteration 66,67 seem to impact vaccine efficacy against their respective drug targets. It has been consistently shown that oxycodone is a more immunogenic hapten core than hydrocodone, despite a minor structural difference consisting of a -OH vs -H at the C14 position on the morphinan structure.…”
Section: ■ Discussionmentioning
confidence: 91%
“…To prepare the vaccine, they used a heroin-mimicking molecule in which they replaced several hydrogen atoms with deuterium and found that the new vaccine was significantly improved as shown from titer, affinity, specificity, and behavioral models including antinociception and drug biodistribution (Figure 9). 413…”
Section: Drug Developmentmentioning
confidence: 99%
“…Activation was monitored by LC–MS, and the activated hapten was subsequently coupled to an immunogenic carrier protein. We implemented keyhole limpet hemocyanin (KLH) as the carrier protein, because it has been used in prior clinical trials and has been successfully utilized in other immunopharmacotherapeutic vaccines. , Application of KLH was cost-effective and convenient, but future studies geared for clinical application will require a more suitable carrier protein …”
Section: Results and Discussionmentioning
confidence: 99%